COPING WITH BURDENING SITUATIONS IN DIALYZED PATIENTS - Gurková, Elena; Michnáčová, Andrea (Profese Online, 2008)
Ineffective coping is a nursing diagnosis of the NANDA International classification system. Diagnostic phase of this problem focused on ineffective coping strategies identification in relation to changes in health status. The aim of this work was to identify coping strategies witch are used by patients on haemodialysis. Authors of this work aimed to determine the significant differences in coping strategies in relation to age, gender and length of therapy. In order to classify coping strategies authors used a standardized questionnaire called Brief COPE by Carver. (1997) They found out on the sample size of 45 respondents, that the most commonly used strategy was acceptance within the whole group of respondents. Authors found the following statistically significant differences in using coping strategies: considering age: in the strategy focussing on positive reinterpretation, growth and self-accusation; considering gender: in the strategy using religion, in the strategy focussing on the venting of emotions, in the strategy focussing on self-accusation. Considering family status, neither considering the time from filing the respondents for dialysis treatment we did not find any statistically significant differences. Psychological reactions are different in different people. The situation in which the patients have found themselves burdens them to a different extent and imposes upon them different requirements. If we want to help such a patient professionally, it is necessary that we know these strategies, thanks to which we can start the following long-term cooperation and motivate them to undergo the treatment.
Keywords: coping; haemodialysis; Brief COPE; coping strategies